Adsorption Of 3-And 4-Aminopyridine On Loughlinite-An IR Spectroscopic Study - AKYÜZ, SEVİM; AKYÜZ, ZEKİ TANIL (Elsevier Science Bv, Po Box 211, 1000 Ae Amsterdam, Netherlands, 2010)
In this study adsorption of 3- and 4-aminopyridine on loughlinite (Na-sepiolite) have been investigated by FT-IR spectroscopy. Spectroscopic results indicate that sorbed aminopyridine molecules onto loughlinite are coordinated to Lewis acidic centers, zeolitic/bound water molecules, and surface silanol groups by hydrogen bonding interaction through pyridine ring nitrogen lone pairs. Some of the adsorbed molecules coordinate to Bronsted acidic centers and aminopyridinium cationic surface species are also generated. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: adsorption; aminopyridine; clay minerals; IR spectroscopy; loughlinite; FT-IR; tetracyanonickelate complexes; na-sepiolite; anatolia; montmorillonite; 3-aminopyridine; 2-aminopyridine; spectra; emme; kil mineralleri